2014
DOI: 10.1111/cmi.12312
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase in human neutrophil host defence

Abstract: Summary Human neutrophils represent the predominant leucocyte in circulation and the first responder to infection. Concurrent with ingestion of microorganisms, neutrophils activate and assemble the NADPH oxidase at the phagosome, thereby generating superoxide anion and hydrogen peroxide. Concomitantly, granules release their contents into the phagosome, where the antimicrobial proteins and enzymes synergize with oxidants to create an environment toxic to the captured microbe. The most rapid and complete antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
149
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(153 citation statements)
references
References 116 publications
2
149
0
2
Order By: Relevance
“…It is possible that lactoferrin contributes to P. stomatis killing by inhibiting bacterial growth. Myeloperoxidase, present in the matrix of azurophil granules, is a key enzyme that uses hydrogen peroxide as a substrate to generate the toxic antimicrobial component hypochlorous acid (HOCl) (44). Our data showed that both specific and azurophil granules were efficiently recruited to P. stomatis phagosomes.…”
Section: Discussionmentioning
confidence: 77%
“…It is possible that lactoferrin contributes to P. stomatis killing by inhibiting bacterial growth. Myeloperoxidase, present in the matrix of azurophil granules, is a key enzyme that uses hydrogen peroxide as a substrate to generate the toxic antimicrobial component hypochlorous acid (HOCl) (44). Our data showed that both specific and azurophil granules were efficiently recruited to P. stomatis phagosomes.…”
Section: Discussionmentioning
confidence: 77%
“…PAD4 may not be necessary for PMA-induced NETs (23), and PMA does not induce a rise in intracellular Ca 2+ that could activate PAD4 (24). MPO, which converts hydrogen peroxide to hypochlorous acid (25), appears to be required for PMA-induced NETosis (26). MPO binds histones and assists elastase during PMA-induced NETosis (8).…”
Section: Inducers Of Net Formationmentioning
confidence: 99%
“…MPO catalyzes the conversion from hydrogen peroxide to hypochlorous acid and is essential for optimal oxygen-dependent antimicrobial activity. 1,2 In the endoplasmic reticulum (ER), glycosylated MPO precursors are chaperoned by the calreticulin (CALR)-calnexin (CNX) cycle. [3][4][5] Both CALR and CNX are lectins that transiently bind to virtually all newly generated glycoproteins (GPs), and their specificity for GPs is mediated by a binding site that recognizes the oligosaccharide Glc 1 Man 9 GlcNAc 2 .…”
Section: Introductionmentioning
confidence: 99%